AVALIAÇÃO DA APRENDIZAGEM EM MATEMÁTICA: UMA CONTRIBUIÇÃO PARA UM CURSO DE LICENCIATURA EM MATEMÁTICA - Tonin, Ademilson Marcos (2016)
This study is a qualitative research about learning assessment concepts used by Mathematics teachers. The trial took place at the Mathematics Degree Course in Federal Institute of Rio Grande do Sul (Instituto Federal do Rio Grande do Sul - IFRS) - Campus Osório. The purpose was to check if the pedagogical practices were based on conservative methods of teaching. The strategy used to collect data follows questionnaires and interviews, in addition to the analysis of the documents that guide the evaluation practices used in the course. Content analysis was used to interpret data. The result achieved in this particular situation showed that education plan and guiding documents work in the same line. Concerning learning assessments and teacher practices, it is possible to notice some innovation discourse in order to use a critical concept of teaching, but there are still some conservative evaluation practices, based on traditional education concepts.